Visitation patterns of cultivated Tetragonula biroi colonies on Xanthostemon chrysanthus flowers - Nur Apriatun Nafisah; Fathimah Nurfithri Hashifah; Christosie Immanuel Wahyudi (Bioma : Berkala Ilmiah Biologi, 2026)
Tetragonula biroi is a cultivated stingless bee widely used in meliponiculture due to its high honey and propolis production. One recommended forage plant is Xanthostemon chrysanthus, yet quantitative data on visitation dynamics and environmental drivers remain limited. This study addressed the following research questions Does visitation frequency of T. biroi vary across time of day? And which environmental factors influence visitation activity? We hypothesized that visitation frequency would peak under optimal morning microclimatic conditions and correlate positively with temperature and light intensity. The study was conducted in June 2025 in Banyumas, Central Java, using 10 managed colonies and flowering X. chrysanthus trees observed over 12 sampling days. Bee visitation was recorded at 10 minute intervals during morning (07.00 – 10.00), midday (11.00 – 13.00), and afternoon (14.00 – 16.00) periods. Data were analyzed using one-way ANOVA and Principal Component Analysis (PCA). Visitation frequency showed a descriptive peak in the morning (6.11 ± 2.25 visits/10 min) but did not differ significantly among periods (F = 0.850; p = 0.437). Visit duration displayed a similar non-significant pattern (F = 0.541; p = 0.587). The number of flowers visited increased from morning to afternoon, indicating compensatory exploratory foraging as nectar availability declined. PCA revealed that temperature and light intensity were positively associated with visitation frequency, whereas humidity was negatively associated. These findings indicate that T. biroi exhibits flexible foraging behavior across a broad range of microclimates. In practice, placing colonies in warm, moderately humid environments may optimize foraging efficiency and support stingless bee productivity.